Impact of Distance Learning on Mental Health During COVID-19: A Review - Salih, Yasir; Ibrahim, Riza Andrian (Research Collaboration Community (Rescollacom), 2021)
The COVID-19 pandemic requires physical activity to reduce its spread. Physical restrictions have a direct impact on the closure of school activities. Distance learning is an alternative for school activities that do not require direct learning communication in one room. However, distance learning can have an impact on students' mental health. This study aims to determine the impact of distance learning during the COVID-19 pandemic on students' mental health.